When all is unequal, the rich get dominant: Inequality leads to expectations of dominant leadership among those high in SES - Anita Schmalor; Eric J. Mercadante; Jessica L. Tracy; Steven J. Heine (PLoS ONE, 2025)
People of higher SES have been found to behave more dominantly than people of lower SES. We tested the hypothesis that this difference is exacerbated under conditions of high economic inequality, when the income/wealth difference between those of low and high SES becomes greater. Across four studies (N =  2,739), using both experiments that manipulate perceived inequality (Studies 1a, 1b, and 3) and a correlational study that measures perceived inequality (Study 2), we find evidence that people expect others and themselves to become more dominant if they are of high as opposed to low SES, and this difference is most extreme when economic inequality is perceived to be high.